HUKUM KOMUNIKASI DI ERA DIGITAL: KAJIAN PUSTAKA ATAS ATURAN HUKUM YANG MENGATUR KEBEBASAN, BATAS, DAN TANGGUNG JAWAB DALAM PENYAMPAIAN PESAN MELALUI MEDIA CETAK, ELEKTRONIK, DAN TELEKOMUNIKASI - Gunawan Widjaja (ADISAM PUBLISHER, 2026)
This study examines the legal framework of communication in the digital age, focusing on the rules governing freedom, limits, and responsibilities in the delivery of messages through print, electronic, and telecommunications media. Through a normative-analytical literature review approach, this study analyses the constitution, human rights laws, the Press Law, the Broadcasting Law, the Telecommunications Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law as the legal basis for freedom and restrictions on communication. The results of the study show that freedom of expression in the digital space is an extension of constitutional rights that remains limited by legal norms in the interests of security, public order, and morality. In addition, legal responsibility is not only attached to individual users, but also to press institutions, digital platform operators, telecommunications service providers, and the government. The integration of legal norms and digital communication ethics is key to maintaining a balance between freedom of communication, public protection, and respect for human rights in Indonesia.